A comprehensive overview of patient journey and management decision pathway for myelofibrosis in India: INLAND survey - Prantar Chakrabarti; Abhay Bhave; Claire Harrison; Tulika Seth; Vikram Mathews; Disha Shetty (BMC Cancer)
Abstract Background Myelofibrosis is a myeloproliferative neoplasm characterized by stem cell-derived clonal myeloproliferative and anomalous production of cytokines with genetic mutations in the JAK/STAT signalling pathway playing a distinctive role in its pathophysiology. Diagnosis of MF presents a challenge due to vague and overlapping symptoms. The present strategy for managing MF is not well defined and relies on a symptomatic approach. Ruxolitinib is the first drug approved by the United States Food and Drug Administration in 2011. Drug Controller General of India approved Ruxolitinib in 2013 as a first-line treatment in patients with MF. This comprehensive survey aims to understand the MF patient journey and the perceptions/practices of Indian hematologists/oncologists regarding diagnosis, prognosis, and disease management of myelofibrosis. Methods A cross-sectional, multicentric, qualitative survey was conducted across 17 Indian cities from October 2021 to November 2021. One-on-one telephonic interviews were conducted using a structured questionnaire based on the study objective. Descriptive statistics were used to analyse the obtained data. Results Overall, 50 physicians and 154 patients (primary MF: 51, post-PV: 78 and post-ET: 25) completed the survey. The most common symptoms reported by patients and physicians at the time of diagnosis were, abdominal pain/discomfort (81% vs. 70%), fatigue/tiredness/weakness (77% vs. 73%) and fever (54% vs. 48%). A 10-month delay was observed from the symptom onset to the final diagnosis and a further 9-month lag from final diagnosis to treatment initiation. In our survey, the physicians preferred Hydroxyurea (88%), blood transfusion (82%) and Ruxolitinib (78%) as the treatment regimen. The majority of the patients were aware of their treatment. Hydroxyurea constituted the predominant treatment option (n = 85); however, satisfaction was highest with Ruxolitinib (50%, n = 13). The physicians considered improving overall survival as an important treatment goal, while patients prioritized symptom relief. Conclusion The survey highlights the importance of understanding symptom burden and treatment goal perceptions in shaping management decisions. The results emphasize the need to align the physicians and patients on the actual treatment outcomes through patient education. Strengthening this alignment will enhance treatment adherence, improve patient satisfaction, and ensure better clinical outcomes, ultimately leading to a more patient-centred approach to managing the disease.